What Should a Political Scientist Know About Religion? - Piotr Mazurkiewicz (Chrześcijaństwo-Świat-Polityka)
A political scientist will not see any reasons for becoming seriously interested in the phenomenon of religion unless he finds religion to be a lasting phenomenon in the history of civilization. The first question that needs to be answered in order to talk reasonably about the borderland between religion and politics is the issue of what religion is, and how historical religions essentially differ from one another. One may then study, for example, the political effectiveness of religious motivation. The other question is whether a functional approach to religion in the context of political science is sufficient. The author suggests that it should be replaced with a semi-substantial approach. It requires from a political scientist to understand the essence of a particular religion and the extent to which certain social consequences of religious beliefs (e.g. polygamy, religiously motivated violence, separation between religion and politics) are related to its essence, and to what extent such relationship is merely accidental.